Malaysia’s Indisputable Sovereignty Over Sabah - Hazmi Mohd. Rusli; Mohd Ridwan Talib; Rahtami Susanti; Ika Ariani Kartini (Kosmik Hukum, 2023)
On Jan 22, 1878, an agreement was signed between the Sultan of Sulu with two British agents, Alfred Dent, and Baron von Overbeck, ceding North Borneo to the British in return for the payment of cession money of 5,000 Malayan dollars annually to the Sultan. The payment was increased to 5,300 dollars per year when nearby islands from Banggi Island to Sibuku Bay were also ceded. Sabah was briefly placed under Japanese rule during World War II and later reverted back to British rule upon Japanese surrender in 1945. Sabah remained a British crown colony until it gained independence within Malaysia in 1963. As a component state of the Federation, Malaysia has invested billions of Ringgit to develop Sabah, establishing a working government to administer this territory. The heirs of the forgone Sulu Sultanate have not done much to display that they are in fact the sovereign rulers of Sabah. This article discusses on the recent issue pertaining to the ‘Sulu state arbitration’ requesting Malaysia to pay compensation to the heirs of the Sulu Sultanate for exercising sovereignty over Sabah from the purview of international law and state sovereignty.  The heirs of the defunct Sulu Sultanate are adamant that Sabah is still ‘part of their territory’. This article concludes that Sabah is recognized globally as part of Malaysia, in no way Malaysia is obliged to entertain claims of descendants of a long-lost sovereign. As a full member of the United Nations, Malaysia is an independent sovereign state and its sovereignty over Sabah must be respected.Keywords: Sabah, State Sovereignty, International Law, Territorial Integrity, Federation of Malaysia, Sultanate of Sulu